1995
DOI: 10.1111/j.1600-051x.1995.tb00120.x
|View full text |Cite
|
Sign up to set email alerts
|

Doxycycline inhibits neutrophil (PMN)‐type matrix metalloproteinases in human adult periodontitis gingiva

Abstract: Doxycycline inhibits neutrophil (PMN)-type matrix metalloproteinases in human adult periodontitis gingiva. J Clin Periodontol 1995; 22: 100^109. © Mutiksgaard, i995.Abstract We previousiy reported tliat low-dose doxycycline (DOXY) therapy reduces host-derived coliagenase activity in gingival tissue of aduit periodontitis (AP) patients. However, it was not ciear wiiether this in vivo effect was direct or indirect. In the present study, iniiamed human gingival tissue, obtained from AP patients during periodontal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
1
14

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 240 publications
(175 citation statements)
references
References 43 publications
(53 reference statements)
5
155
1
14
Order By: Relevance
“…The gingival extracts were analyzed for collagenase activity and the results showed that doxycycline significantly reduced collagenase activity in gingiva and GCF of periodontal pockets (7). It has been shown that MMPs in inflamed gingival tissue and GCF of adult periodontitis patients, originating from PMNs, can be directly inhibited by doxycycline (8).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The gingival extracts were analyzed for collagenase activity and the results showed that doxycycline significantly reduced collagenase activity in gingiva and GCF of periodontal pockets (7). It has been shown that MMPs in inflamed gingival tissue and GCF of adult periodontitis patients, originating from PMNs, can be directly inhibited by doxycycline (8).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the non-antimicrobial properties of the drug have a therapeutic potential. These agents can inhibit pathologic collagenolysis by blocking mammalian collagenases and other matrix-degrading metalloproteinases and thereby inhibit connective tissue breakdown (7,8). In one of the studies, patients with moderate chronic periodontitis were administered doxycycline for 2 weeks prior to a full-thickness flap procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The selected drugs have different structures and pharmacological activities, but all share such inhibiting effect [3][4][5][6][7][8][9]. Six ligands were tested: three oxicans, namely Meloxicam, Tenoxicam and Piroxicam, tetracycline, doxycycline and sodium alendronate.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibition of excessively produced MMPs is the major goal in host-modulation therapy (Golub et al, 1995). Although the inhibition of MMPs is thought to decrease tissue degradation, studies on MMP knock-out animal models indicated that MMP-deficient animals are more prone to periodontal degradation in comparison with non-deficient controls (Kuula et al, 2009).…”
Section: Research Articlementioning
confidence: 99%